Recidivism Rates of Treated, Non-Treated and Dropout Adolescent Who Have Sexually Offended: a Non-Randomized Study - Carpentier, Julie; Proulx, Jean (Frontiers in Psychology, 2021)
The primary objective of this study was to evaluate the effectiveness of a cognitive-behavioural treatment in reducing recidivism by adolescents who have sexually offended (ASO). A secondary objective was to determine whether typologies based on victim age (child, adult/peer, mixed) and relationship (intrafamilial, extrafamilial, intra/extrafamilial) discriminate ASO in terms of response to treatment and recidivism. The sample comprised 327 adolescents 12-18 years old (M = 15.8 years, SD = 1.9) who were evaluated in an outpatient clinic after committing a contact sexual assault. Official data on recidivism (criminal charges) was collected after a follow-up period of 12-162 months (M = 7.8 years, SD = 32.2). Survival analysis indicated that adolescents who completed treatment (n = 62) had a recidivism rate for violence (including sexual violence) almost half that of adolescents who had either not completed the treatment or not received treatment (n = 261) (16.1% vs. 30.7%). Neither of the two typologies studied had any effect on the completion of treatment. However, sexual aggression against adults/peers was associated with an increased probability of violent re-offending. These results confirm the effectiveness of this cognitive-behavioural treatment —which targets risk factors associated with sexual aggression as well as those associated with violence in general—in ASO.